The curious incident of the missing cleaner - Bulkeley, Rip (Polar Record, 2009)
ABSTRACT The first woman to work as a professional scientist in Antarctica was Mariya Vasilyevna Klyonova, during the first Soviet Antarctic Expedition of 1955–1957. Other women were crew members on the icebreakers Lena and Ob’ . There is an outside possibility that there was more to one of them than meets the eye. But we shall never know.